History and geography of human genetic diversity I - Cavalli-Sforza, Luigi Luca (Henry Stewart Talks, 2007)
Four major factors of evolution: mutation, natural selection, drift, migration, Role of demography in the quantitative study of evolution, Drift: the Parma Valley study, Equilibrium of migration and drift, Founders' effect, Reconstructing evolutionary history of a population, Evidence of the importance of drift from molecular evolution, Molecular evolution of proteins, Trees with proteins and trees with DNA, Phylogeographic analysis, Microsatellites, Graphic presentation of evolution data by principal components analysis